Severity of childhood maltreatment predicts reaction times and heart rate variability during an emotional working memory task in borderline personality disorder: basic research article - Krause-Utz, Annegret; Walther, Julia-Caroline; Kyrgiou, Akrivi I.; Hoogenboom, William; Alampanou, Myrto; Bohus, Martin; Schmahl, Christian; Lis, Stefanie (European journal of psychotraumatology, 2022)
Background: Difficulties in emotion regulation are a core symptom of borderline personality disorder (BPD) and often interfere with cognitive functions, such as working memory (WM). Traumatic childhood experiences, including severe maltreatment, can contribute to emotion dysregulation, possibly mediated by changes in high-frequency heart rate variability (HF-HRV). However, it is not yet entirely understood if HF-HRV alterations underlie impaired WM during emotional distraction in BPD and if this is related to traumatic childhood experiences and to comorbid post-traumatic stress disorder (PTSD).Objective: Our aim was to investigate performance (reaction times, RTs) and HF-HRV during an emotional working memory task (EWMT) in relation to childhood maltreatment severity and comorbid PTSD in BPD.Method: Eighty-one women (n = 28 healthy controls (HC) and n = 53 BPD patients of which n = 18 had comorbid PTSD) performed an adapted Sternberg item recognition WM task with neutral and negative social cues (interpersonal scenes from the International Affective Picture System (IAPS), and neutral, fearful, and angry faces) as distractors. Dependent variables were RTs of correct trials and HF-HRV. Childhood maltreatment was assessed with the Childhood Trauma Questionnaire.Results: Compared to healthy participants, patients with BPD showed prolonged RTs across all distractor conditions with social cues, regardless of their emotional valence. Patients with BPD, especially those with PTSD, demonstrated reduced HF-HRV both at rest and during EWMT. Severity of childhood maltreatment predicted longer RTs and lower HF-HRV during the EWMT.Conclusions: Findings suggest that adverse childhood experiences accelerate difficulties in shifting attention away from social information and that these are more pronounced in individuals with BPD. Reduced HF-HRV (low parasympathetic-tonus) may be an important psychophysiological mechanism underlying impaired WM in the presence of distracting social cues in patients with BPD, especially in those with comorbid PTSD.HIGHLIGHTS This study provides evidence that childhood maltreatment experiences are associated with hypersensitivity to social information and reduced high-frequency heart rate variability during a working memory task in borderline personality disorder.
Gesehen am 19.06.2023